Quaranta, Francesco. Preti sposati nel Medioevo. Cinque apologie. Torino: Claudiana, 2000, 148 pp - Hubeñak, Florencio (2002)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina